Neuromuscular induced phonation in a human ex vivo perfused larynx preparation - Berke, Gerald (Acoustical Society of America, 2013)
Considering differences in laryngeal anatomy, degree of control, and range of voice qualities between animals and humans, investigations of the neuromuscular process of voice control are better conducted using a living human larynx in which parametric stimulation of individual laryngeal muscles is possible. Due to difficulties in access and monitoring of laryngeal muscle activities, such investigations are impossible in living human subject experiments. This study reports the recent success in developing an ex vivo perfused human larynx model, which allows parametric muscle stimulation and observation of its influence on phonation of a virtually living human larynx in a well-controlled laboratory environment.